Spectrophotometric Determination of Epinephrine in Pharmaceutical Preparations Using Praseodymium as Mediating Metals (Baghdad Science Journal, 2025)
A simple, accurate and sensitive spectrophotometric method for the determinaion of epinephrine is described . The method is based on the coordination of Pr (III) with epinephrine at pH 6. Absorbance of the resulting orange yellow complex is measured at 482 nm . A graph of absorbance versus concentrations shows that beer 's low is obeyed over the concentration range (1-50)mg.ml-1 of epinephrine with molar absorpitivity of ( 2.180x103 L.mol-1.cm-1 ), a sandell sensitivity of (0.084 mg.cm-2 ), a relative error of (-2.83%) , a corrolation coffecient (r= 0.9989) and recovery % ( 97.03 ± 0.75 ) depending on the concentration.This method is applied to analyse EP in several commercially available pharmaceutical preparations using direct methods .All statistical calculations are implemented via a Minitab software version 11.